2010
DOI: 10.1371/journal.pone.0009523
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Processing in Intuitive Perception

Abstract: The process of perception requires not only the brain's receipt of sensory data but also the meaningful organization of that data in relation to the perceptual experience held in memory. Although it typically results in a conscious percept, the process of perception is not fully conscious. Research on the neural substrates of human visual perception has suggested that regions of limbic cortex, including the medial orbital frontal cortex (mOFC), may contribute to intuitive judgments about perceptual events, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
(45 reference statements)
3
17
0
Order By: Relevance
“…(Overgaard et al, 2006) A few years before, Petra Stoerig conducted a research on the functional vision system and levels of perception, in which she already suggested "a concept of dissociable levels of perception." (Stoerig & Brandt, 1993) And in a survey about intuitive perception, Phan Luu (Luu et al, 2010) and his team agreed that the "process of perception requires not only the brain's receipt of sensory data but also the meaningful organization of that data in relation to the perceptual experience held in memory," bearing in mind that although it results in a "conscious perception, the perception process is not fully conscious" before the perception culminates "the initial representation of gist may support intuitive judgments about the ongoing perceptual process." (id.…”
Section: Mind's Trichotomy As Interpretantmentioning
confidence: 99%
“…(Overgaard et al, 2006) A few years before, Petra Stoerig conducted a research on the functional vision system and levels of perception, in which she already suggested "a concept of dissociable levels of perception." (Stoerig & Brandt, 1993) And in a survey about intuitive perception, Phan Luu (Luu et al, 2010) and his team agreed that the "process of perception requires not only the brain's receipt of sensory data but also the meaningful organization of that data in relation to the perceptual experience held in memory," bearing in mind that although it results in a "conscious perception, the perception process is not fully conscious" before the perception culminates "the initial representation of gist may support intuitive judgments about the ongoing perceptual process." (id.…”
Section: Mind's Trichotomy As Interpretantmentioning
confidence: 99%
“…In distinction, intuitive decision-making relies upon a more holistic approach inprocessing to continue judging for planned results as the external problem space changes (Evans: 2008). Intuition is a rapid, non-conscious, indication to the existence of meaningful information detected through one or more sensory modalities (Luu et al: 2010).…”
Section: Theme 6 Open Strandmentioning
confidence: 99%
“…This unconscious organization of incoming information may elicit a feeling or impression of a solution (Luu et al: 2010), which introduces insight or a rapid awareness.…”
Section: Theme 6 Open Strandmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that this process involves local and distributed neuronal net works encompassing projection cortical fields, the extrastriate cortex, the prefrontal cortex, and limbic structures of the brain [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It follows that the pos sibility of recognizing objects of different complexities is determined by the extent and pattern of involvement of modal specific structures in the analysis and pro cessing of visual information and regulatory systems modulating the functional activity of various cortical zones.…”
mentioning
confidence: 99%